Numerical investigation of the effect of plane boundary on two-degree-of-freedom of vortex-induced vibration of a circular cylinder in oscillatory flow. (15th January 2018) - Munir, Adnan; Zhao, Ming; Wu, Helen; Ning, Dezhi; Lu, Lin
Abstract: The laying of subsea pipelines often produces situations where the pipeline is suspended above the seabed due to local erosion of sediment. In this paper, flow induced vibration of a circular cylinder close to a plane boundary in an oscillatory flow is studied through two-dimensional numerical simulations. The circular cylinder and the plane boundary represents a pipeline and the seabed, respectively. It is found that the plane boundary affects the vibration amplitude in the cross-flow direction significantly. The vibration in the vertical direction ceases if reduced velocity exceeds 6 for KC = 5 and 12 for KC = 10, respectively. The vibration in the cross-flow direction stops when the reduced velocity exceeds a critical value because the effective KC number and the effective reduced velocity, which are both based on the relative velocity of the cylinder to the fluid motion, are extremely small. For KC = 10, the vortex shedding is found to be in one pair regime for most of the reduced velocities and non-vortex shedding regime exists at large reduced velocities. Because the shear layers generated from the plane boundary attract the vortices generated from the cylinder, vortex shedding occurs only at the bottom side of the cylinder. Highlights: VIV of a cylinder near a plane boundary is studied numerically. The plane boundary does not affect the lock-in range of the reduced velocity. The plane boundary has a significant influence on the vibration amplitude in the cross-flow direction. The vibration in the y -direction ceases after reduced velocity exceeds a critical value. The vortex shedding only occur at the boundary side of the cylinder.